PENGARUH MEDIA PEMBELAJARAN BERBASIS GAMIFIKASI TERHADAP HASIL BELAJAR SISWA DI SD NEGERI 85 PALEMBANG - Nur ‘Azizah Kallabe; Karoma; Arvin Efriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study addresses the issue of low student learning outcomes driven by conventional, teacher-centered instructional media that fail to maintain the attention span of elementary school students. The purpose of this research is to empirically examine the effect of gamification-based learning media on student learning outcomes at SD Negeri 85 Palembang. This study employed a quantitative approach with a quasi-experimental design, specifically the Nonequivalent Control Group Design. Sampling was conducted using purposive sampling technique, involving 27 students as the research sample. Data collection was executed through pretest and posttest instruments, which were analyzed using Paired Samples T-Test via IBM SPSS Statistics. The results of the Shapiro-Wilk normality test indicated that the pretest (0.302) and posttest (0.086) data were normally distributed (p>0.05). Furthermore, the Paired Samples T-Test yielded a t-value of −26.494 with a two-sided significance level (p-value) of <0.001, which is lower than the significance threshold (α=0.05). Descriptive analysis showed a notable increase in the mean score from 64.93 in the pretest to 79.37 in the posttest. Therefore, it can be concluded that the application of gamification-based learning media exerts a positive and significant effect on student learning outcomes at SD Negeri 85 Palembang, effectively fostering a dynamic and high-performing cognitive learning environment